Chas izbiratelia . Chas izbiratelia . The Electorate's Hour . Час избирателя - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Presentations by the electoral association "The Future of Russia - New Names" and the Liberal Democratic Party of Russia. Featured in the program: Zhirinovskii, Vladimir Vol'fovich (Politician) Выступления избирательного объединения "Будущее России - Новые Имена" и Либерально-Демократической Партии России. В программе участвуют: Жириновский, Владимир Вольфович (Политик)